Immortal Love: Metin Erksan Reimagines Wuthering Heights. (3rd July 2019) - Kaya, Nilay; Tekcan, Rana
Abstract : This article aims to look at a Turkish film adaptation of Emily Brontë's Wuthering Heights. The 1966 black-and-white film, directed by the renowned director Metin Erksan, carries the story to a farm on the hills of Bosphorus, Istanbul. Although Erksan emphasizes the issue of class in the film, he is particularly interested in recreating the novel's atmosphere in his own cinematic language. A director very much drawn to dark, destructive love stories throughout his career, Erksan manages to capture 'the spirit' of the novel with the help of his two lead actors. Immortal Love is an example of the avant-garde, at the crossroads of the national and the universal. It is an affirmation of the novel's seemingly endless appeal and inspiration.